The Relationship between RUNX3 Expression, Nursing Strategies and Nutritional Status in Elderly Patients with Advanced Gastric Cancer - Wen SONG; Wenhui TENG; Xinyan SHI; Xiaozhen LIU; Zheng CUI; Zibin TIAN (Tehran University of Medical Sciences, 2017)
Background: The aim of this study was to explore the relationship between nutritional status and expression of RUNX3 in gastric cancer cells and to investigate the effects of nursing strategies on the nutritional status of elderly patients with advanced gastric cancer. Methods: Forty-eight elderly patients admitted at Affiliated Hospital of Qingdao University with advanced gastric cancer and 30 healthy controls were selected as subjects from 2014-15. The correlation between RNX3 gene expression and nutritional status of the gastric cancer patients was investigated. The patients with advanced gastric cancer who had low expression of RUNX3 gene were treated with holistic nursing while routine nursing was taken for those patients who had normal or high expression of RUNX3 gene. The nutritional statuses of these patients were evaluated after 3 months of nursing. After a follow-up of 1 year, the influence of different nursing methods on the survival time was evaluated. Results: Compared with normal gastric tissue, the expression of RUNX3 gene and protein in tissues of advanced gastric cancer were significantly decreased (P<0.01). Compared with patients with normal or high expressions of RUNX3, the nutritional statuses of advanced gastric cancer patients with low expressions of RUNX3 were lower (P<0.01). The nutritional statuses of patients with low expressions of RUNX3 were notably improved after holistic nursing, becoming equivalent to those with normal or high expression of RUNX3 who received routine nursing (P>0.05). The survival time of patients with low expression of RUNX3 who received holistic nursing were similar to patients with normal or high expression of RUNX3 who received routine nursing (P>0.05). Conclusion: RUNX3 is correlated with the occurrence and development of advanced gastric cancer. The low nutritional status of elderly advanced gastric cancer patients with low expressions of RUNX3 can be significantly enhanced by holistic nursing, thereby prolonging survival time.